GDF11 ameliorated myocardial ischemia reperfusion injury by antioxidant stress and up-regulating autophagy in STZ-induced type 1 diabetic rats - Bin,Zhou (2019)
Abstract Purpose: To investigate whether GDF11 ameliorates myocardial ischemia reperfusion (MIR) injury in diabetic rats and explore the underlying mechanisms. Methods: Diabetic and non-diabetic rats subjected to MIR (30 min of coronary artery occlusion followed by 120 min of reperfusion) with/without GDF11 pretreatment. Cardiac function, myocardial infarct size, creatine kinase-MB (CK-MB), lactate dehydrogenase (LDH), superoxide dismutase (SOD) 15-F2tisoprostane, autophagosome, LC3II/I ratio and Belcin-1 level were determined to reflect myocardial injury, oxidative stress and autophagy, respectively. In in vitro study, H9c2 cells cultured in high glucose (HG, 30mM) suffered hypoxia reoxygenation (HR) with/without GDF11, hydrogen peroxide (H2O2) and autophagy inhibitor 3-methyladenine (3-MA) treatment, cell injury; oxidative stress and autophagy were assessed. Results: Pretreatment with GDF11 significantly improved cardiac morphology and function in diabetes, concomitant with decreased arrhythmia severity, infarct size, CK-MB, LDH and 15-F2tisoprostane release, increased SOD activity and autophagy level. In addition, GDF11 notably reduced HR injury in H9c2 cells with HG exposure, accompanied by oxidative stress reduction and autophagy up-regulation. However, those effects were completely reversed by H2O2 and 3-MA. Conclusion: GDF11 can provide protection against MIR injury in diabetic rats, and is implicated in antioxidant stress and autophagy up-regulation.